1945 Genenal Election: Dynamics And Dark Side In The Process Of Implementation - Rooby Pangestu Hari Mulyo Rooby; Siti Fatimah (Journal of Economics, Social, and Humanities, 2023)
The 1955 general election was the first election held in Indonesia. This election is considered as the most democratic election by the majority of Indonesian people and this has also been strengthened a lot in the form of scientific writings. Departing from this, the author tries to examine in depth the assumptions that have been conveyed by the majority of Indonesian people both in academic forums and non-academic forums regarding their legitimacy. Furthermore, this research is included in library research and the research approach used is a historical approach. The results of this research are: 1. In the 1955 Election there were quite harsh dynamics, the big parties competed to get high votes by attacking each other. Throwing each other down in the campaign process which is also a place to hook the masses; 2. The 1955 election which we consider to be the most democratic election was actually based more on the number of voters and valid votes counted in the 1955 election. It was recorded that as many as 92% of the people exercised their right to vote in the 1955 election. But on the other hand, there were still frauds committed If it happens, the fraud is not only carried out by party elements, or persons who serve as lurah, but also carried out by the election management committee.